The contributions of coastal small-scale fisheries toward the sustainable development goals: a Kenyan Case Study - E. N. Fondo; R. E. Bitoun; E. N. Kimani; C. N. Munga; N. Wambiji; N. Ishmael; D. Mwandikwa; B. Busolo; M. Okeri; S. Abas; G. W. Maina; R. Devillers (npj Ocean Sustainability)
Abstract Small-scale fisheries (SSFs) contribute significantly to the economies of coastal developing nations, offering employment and food, and supporting sustainable development goals (SDGs). Despite increasing focus on SSFs, data, and knowledge gaps persist in SSFs research and their contribution to SDGs. Ten fisheries were assessed in Kenya for their contributions to 12 SDGs, highlighting different levels of contributions. Small pelagic and shrimp fisheries display higher overall contributions to SDGs, appearing to perform strongly in more SDGs, while handline and octopus fisheries display lower contributions to SDGs. Specific contributions can vary depending on the characteristics of individual fisheries, such as their structures and markets. This study provides valuable insights from an under-represented part of the world on the under-researched topic of SSFs and SDGs. It also contributes significantly to research on sustainable development in developing coastal nations and highlights gaps and areas for improvement in achieving the SDGs within the context of SSFs.